التطورات الحديثة في الخصائص البنيوية للأغشية الرقيقة SnO₂ وتطبيقاتها - بوخزنه إيمان; عماري وفاء; مباركي وفاء (جامعة الشهيد حمه لخضر بالوادي, 2025)
Tin dioxide (SnO₂) is a chemical compound composed of tin (Sn) and oxygen (O). It is widely used in modern technological applications, particularly in the fields of electronics and renewable energy, thanks to its unique properties. Therefore, this work focuses on studying its structural and chemical properties and evaluating its antibacterial activity. X-ray diffraction (DRX) analysis revealed that the films possess a polycrystalline structure and a preferential (200) orientation. The results also demonstrated an improvement in crystallinity over the years (from 2016 to 2018), with peak intensity increasing with a decrease in their amplitude. Results of the FT-IR spectroscopy study revealed a distinct peak at 500 cm⁻¹, indicating the vibration of the Sn–O bond and the formation of pure tin oxide. Furthermore, antibacterial activity tests confirmed the effectiveness of these films against Escherichia coli, demonstrating the potential of this material for environmental sterilization and disinfection applications such as water treatment or the manufacture of antimicrobial surfaces أكسيد القصدير الثنائي (SnO₂) هو مركب كيميائي يتكون من القصدير (Sn) والأوكسجين (O)، ويُستخدم على نطاق واسع في التطبيقات التكنولوجية الحديثة خاصة في مجالي الإلكترونيات والطاقات المتجددة، وذلك بفضل خصائصه الفريدة. لدى فقد تم الاهتمام خلال هذا العمل بدراسة خصائصه البنيوية والكيميائية وتقييم نشاطه المضاد للبكتيريا. بين تحليل حدود الأشعة السينية (DRX) أن الأغشية تمتلك بنية متعددة البلورات وأخذت الاتجاه التفضيلي (200). كما أظهرت النتائج تحسنًا في جودة التبلور عبر السنوات (من 2016 إلى 2018)، حيث زادت شدة الذروات مع انخفاض اتساعها. كما أظهرت نتائج دراسة مطيافية الأشعة تحت الحمراء (FT-IR) وجود ذروة مميزة عند (cm⁻¹)500 تشير إلى اهتزاز رابطة (Sn–O) وتكوين أكسيد القصدير النقي. من جهة أخرى أكدت اختبارات النشاط المضاد للبكتيريا فعالية هذه الأغشية ضد بكتيريا Escherichia coli، مما يُظهر إمكانية استخدام هذه المادة في تطبيقات تعقيم وتطهير بيئي مثل معالجة المياه أو تصنيع الأسطح المقاومة للميكروبات
Mémoires de master en génie chimique 2025
Keywords: Tin dioxide; Thin films; Pyrolysis spray; X-ray diffraction (DRX); Infrared radiation FT-IR; Antibacterial activity.; ثنائي أكسيد القصدير، الأغشية الرقيقة، الرش بالانحلال الحراري، انحراف الأشعة السينية (DRX)، الأشعة تحت الحمراء (FT-IR)، النشاط المضاد للبكتيريا.